2020
DOI: 10.5588/pha.19.0052
|View full text |Cite
|
Sign up to set email alerts
|

Early chest X-ray in persons with presumptive tuberculosis increases Xpert® MTB/RIF diagnostic yield and efficiency

Abstract: Adult presumptive tuberculosis (TB) patients (n = 1690) were screened for TB using a questionnaire, chest X-ray (CXR) and sputum microscopy for acid-fast bacilli (AFB); <named-content content-type="genus-species">Mycobacterium tuberculosis</named-content> culture was performed for 74% of the patients and Xpert® MTB/RIF was done for 17.2%. Among patients recruited, 943 (55.8%) were diagnosed with TB, of whom 870 (92.3%) were bacteriologically confirmed and 73 (7.7%) were clinically diagnosed on the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Also, the TB prevalence among presumptive in this study was similar to the 21% reported from Aba prison in Abia state Nigeria [12] but higher than 9% from Ethiopia [6]. However, these related studies used a symptombased ACF model, which is associated with more number of missed cases when compared to the CAD4TB chest X-ray used in this project [21]. Furthermore, Xpert testing used for this study is superior to sputum microscopy for the diagnosis of TB [21].…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Also, the TB prevalence among presumptive in this study was similar to the 21% reported from Aba prison in Abia state Nigeria [12] but higher than 9% from Ethiopia [6]. However, these related studies used a symptombased ACF model, which is associated with more number of missed cases when compared to the CAD4TB chest X-ray used in this project [21]. Furthermore, Xpert testing used for this study is superior to sputum microscopy for the diagnosis of TB [21].…”
Section: Discussionsupporting
confidence: 68%
“…However, these related studies used a symptombased ACF model, which is associated with more number of missed cases when compared to the CAD4TB chest X-ray used in this project [21]. Furthermore, Xpert testing used for this study is superior to sputum microscopy for the diagnosis of TB [21].…”
Section: Discussionmentioning
confidence: 99%
“…Sputum smear microscopy as one of the phenotypic methods remains the most commonly used test for diagnosis and monitoring of treatment, despite being less sensitive and non-specific for Mycobacterium tuberculosis ( M. tb ), while mycobacterial culture, being identified and applied as the gold standard for TB diagnosis, has the disadvantage of providing results after a substantial period (3–4 weeks). 14 17 …”
Section: Introductionmentioning
confidence: 99%
“…Sputum smear microscopy as one of the phenotypic methods remains the most commonly used test for diagnosis and monitoring of treatment, despite being less sensitive and non-specific for Mycobacterium tuberculosis (M. tb), while mycobacterial culture, being identified and applied as the gold standard for TB diagnosis, has the disadvantage of providing results after a substantial period (3-4 weeks). [14][15][16][17] The tuberculosis molecular bacterial load assay (TB-MBLA) is a reverse transcriptase quantitative real-time polymerase chain reaction (RT-qPCR) of 16S rRNA detection test that quantifies TB bacillary load and is used as a marker of treatment response for patients on anti-TB therapy. 18 The assay is rapid, free of contamination, and can inform the elimination rate of M. tb during treatment.…”
Section: Introductionmentioning
confidence: 99%
“…The geneXpert examination is a rapid test using the automatic polymerase chain reaction (PCR) molecular test. This test can detect the presence of M. tuberculosis and resistance to rifampicin for less than 2 h. New generation technology of automated platforms for molecular diagnosis [ 13 , 14 ]. The standard TB mastoiditis treatment is in accordance with extrapulmonary TB treatment, namely with anti-tuberculosis drugs for at least 6 months.…”
Section: Discussionmentioning
confidence: 99%